Social Behavior of Bureaucrats in Rural Population Administration Services - Ridwan Syam; Sakaria To Anwar; Atma Ras; Ismaniar Risal Basir (International Journal of Qualitative Research, 2022)
Bureaucratic behavior is the main benchmark for achieving effective public services and assesses the government's most visible performance. Every act of bureaucrats always has social motives in providing administrative services. This study aims to determine the form of social behavior of bureaucrats in providing population administration services in rural areas through a sociological perspective. This research is located in Palakka Village, Barru District, Barru Regency. The method used is a qualitative approach with a descriptive type. Data were collected through in-depth interviews with 12 informants in the village. The results of this study indicate that the social background of rural communities is both a supporter and an obstacle to the performance of bureaucrats in rural areas. Social behavior that emerges from bureaucrats in rural areas is more likely to lead to value-oriented rational actions. Every behavior that appears responds to every situation faced in population administration services for people in rural areas.